<h3>Base Change Property</h3><h3 />
The Base Change Property is very helpful in scenarios related to simplifying equations where the logarithmic terms have a varying base.
So to solve an equation, which possesses logarithmic functions, all logarithmic terms must have a similar base.
<h3>What is Base Change Property?</h3><h3 />
This refers to the base formula which is used to write a logarithm of a number with a base that is fixed as the ratio of two logarithms both having the same base but different from the base of the initial or original logarithm.
Change of Base Formula is given as:
![log_{b} a = \frac{Log_{c} a }{Log_{c} b}](https://tex.z-dn.net/?f=log_%7Bb%7D%20%20a%20%3D%20%5Cfrac%7BLog_%7Bc%7D%20a%20%7D%7BLog_%7Bc%7D%20b%7D)
See the link below for more about Base Change Property:
brainly.com/question/15318682
The equation for area of a triangle is A= 1/2bh so a=1/2(12cm)(9.6cm)
Answer:
a =1 and b =2
Step-by-step explanation:
The standard quadratic is written in the form
ax^2 +bx+c =0
x^2 +2x -13 =0
a =1 and b =2
Answer:
1
m = ---
12
Step-by-step explanation:
The formula is y2-y1
---------
x2-x1
(x1,y1) (x2,y2)
(3,-5) (-9,-6)
You get the 2 Y's and subtract them
Do the same with the X's
Y's above , X's below
(y2- y1)
⬇
-6-(-5) -1 1
--------- = ---- = ---- = m
-9-(3) -12 12
⬆
(×2- x1)
This equation is backwards, thats why it was harder to understand. (-9,-6) is farther left and below point (3,-5), making it the REAL first point in the equation.